2014
DOI: 10.3171/2013.10.peds13231
|View full text |Cite
|
Sign up to set email alerts
|

Misdiagnosing recurrent medulloblastoma: the danger of examination and imaging without histological confirmation

Abstract: The screening and detection of recurrent medulloblastoma presents the clinician with significant diagnostic challenges, including the risk of misdiagnosis. The authors present the case of a young girl with a history of a treated standard-risk medulloblastoma that highlights the risk of assuming recurrence has occurred when clinical and/or imaging changes are observed. This girl developed both new clinical deficits and had radiographic evidence of recurrence. She subsequently experienced a complete reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…Indeed, recent evidence has suggested that a number of late medulloblastoma recurrences diagnosed radiologically may be in fact secondary malignant gliomas histologically. 25,26 Finally, the increasing number of 5-year survivors across treatment eras reflects improved 5-year survival from medulloblastoma as a result of improvement in treatment. Although the sample size differs across the decades, comparisons of treatment changes with outcomes across these decades is valid because our cohort represents each era's 5-year survivor population in an unbiased way.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent evidence has suggested that a number of late medulloblastoma recurrences diagnosed radiologically may be in fact secondary malignant gliomas histologically. 25,26 Finally, the increasing number of 5-year survivors across treatment eras reflects improved 5-year survival from medulloblastoma as a result of improvement in treatment. Although the sample size differs across the decades, comparisons of treatment changes with outcomes across these decades is valid because our cohort represents each era's 5-year survivor population in an unbiased way.…”
Section: Discussionmentioning
confidence: 99%
“…Weintraub et al, have also described a 10-year old girl with suspected relapsed medulloblastoma when she presented with new clinical deficits and radiological evidence consistent with recurrence. 19 In this case as well, both clinical and imaging findings completely resolved after treatment with steroids. A definite diagnosis was not established.…”
Section: Introductionmentioning
confidence: 51%
“…A definite diagnosis was not established. 19 The case highlights the risks of assuming recurrence based on clinical and imaging changes alone. In our patient, after a short-lived initial improvement both symptoms and radiological findings worsened when the steroids were weaned.…”
Section: Introductionmentioning
confidence: 99%
“…However, while the majority of primary CNS ET typically show contrast enhancement, the degree of enhancement can be variable, and considering only MB, approximately 11% to 25% do not enhance [ 7 10 ]. In addition, although MRI findings of pia-arachnoidal or focal nodular brain enhancement were previously described as highly specific in the diagnosis of recurrent disease [ 11 ], contrast enhancement may occur as a result of radiation therapy [ 12 , 13 ], thus posing a major diagnostic challenge.…”
Section: Introductionmentioning
confidence: 99%